Patterns of recurrence and impact on survival in patients with clear cell ovarian carcinoma. Issue 7 (September 2019) - Hogen, Liat; Vicus, Danielle; Ferguson, Sarah Elizabeth; Gien, Lilian T; Nofech-Mozes, Sharon; Lennox, Genevieve K; Bernardini, Marcus Q
Abstract : Background: Patients with recurrent clear cell ovarian cancer have poor prognosis and limited effective systemic treatment options. Objectives: To characterize patterns of recurrence and compare overall survival and post-recurrence survival parameters in patients with recurrent ovarian clear cell carcinoma. Methods: Clinical data on patients with ovarian clear cell carcinoma between June 1995 and August 2014 were collected. Patients with clear cell ovarian cancer recurrence were included in this study. Patients with different histologic sub-type, persistent or progressive disease on completion of the initial treatment were excluded. Descriptive statistics, univariate and multivariable analyses, and Kaplan-Meier survival probability estimates were completed. The log-rank test was used to quantify survival differences on univariable analysis. To search for significant covariates related to the overall survival and post-recurrence survival, a univariable Cox proportional hazard model was performed. Results: A total of 209 patients met inclusion criteria. Of these, 61 (29%) patients who were free of disease at completion of the initial treatment had recurrence. Patterns of recurrence were as follows: 38 (62%) patients had multiple-site recurrence, 12 (20%) had single-site recurrence, and 11 (18%) had nodal recurrence only. The median overall survival was 44.7 months (95% CI 33.4 to 64.2) and was significantly associated with pattern of recurrence (p=0.005). The median post-recurrence survival was 18.4 months (95% CI 12.5 to 26.7): 54.4 months (95% CI 11 to 125.5) in single-site recurrence, 13.7 months (95% CI 6.8 to 16.5) in multiple-site recurrence, and 30.1 (95% CI 7.2 to 89) months in nodal recurrence (p=0.0002). In the multivariable analysis, pattern of recurrence was a predictor of post-recurrence survival. Six patients (9.8%) had a prolonged disease-free interval after recurrence (disease-free for more than 30 months after completion of treatment for recurrence). Prolonged recurrences were noted in 4 (33%) of 12 patients with single-site recurrence, 1 (9%) of 11 patients with nodal recurrence, and in 1 (2.7%) of 38 patients with multiple-site recurrence. Three of the six patients with a prolonged disease-free interval after recurrence were treated surgically at the time of recurrence. Conclusion: Ovarian clear cell carcinoma predominantly recurs in multiple sites and it is associated with a high mortality rate and short post-recurrence survival. When recurrences are limited to a single site, or only to lymph nodes, the median post-recurrence survival is longer. Disease-free interval after recurrence is longer in patients with single-site recurrence who are treated surgically at the time of recurrence.